An explicit construction of quantum codes from one-generator generalized quasi-cyclic codes - Yao Yu; Ma Yuena; Li Husheng; Lv Jingjie (MATEC Web of Conferences, 2021)
In this paper, we take advantage of a class of one-generator generalized quasi-cyclic (GQC) codes of index 2 to construct quantum error-correcting codes. By studying the form of Hermitian dual codes and their algebraic structure, we propose a sufficient condition for self-orthogonality of GQC codes with Hermitian inner product. By comparison, the quantum codes we constructed have better parameters than known codes.